2017
DOI: 10.2527/jas.2016.0961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pelleting on survival of porcine epidemic diarrhea virus–contaminated feed

Abstract: Porcine epidemic diarrhea virus (PEDV) is a heat-sensitive virus that has devastated the U.S. swine industry. Because of its heat sensitivity, we hypothesized that a steam conditioner and pellet mill mimicking traditional commercial thermal processing may mitigate PEDV infectivity. Pelleting, a common feed processing method, includes the use of steam and shear forces, resulting in increased temperature of the processed feed. Two thermal processing experiments were designed to determine if different pellet mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 7 publications
1
39
0
1
Order By: Relevance
“…A 1:10 dilution was performed using PBS to create 2,500 mL of 10 5 TCID 50 /mL viral inoculum. Inoculation of the feed used similar procedures as those described by Schumacher et al (2016b) and Cochrane et al (2017) . Briefly in this experiment, inoculation of feed to be used in each of the laboratory scale mixers was performed in 5-kg batches using an additional laboratory scale mixer in which 4.5 kg of PEDV-negative feed was added to the mixer and 500 mL of 10 5 TCID 50 /mL–diluted viral inoculum was added to create 5 kg of 10 4 TCID 50 /g–inoculated feed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 1:10 dilution was performed using PBS to create 2,500 mL of 10 5 TCID 50 /mL viral inoculum. Inoculation of the feed used similar procedures as those described by Schumacher et al (2016b) and Cochrane et al (2017) . Briefly in this experiment, inoculation of feed to be used in each of the laboratory scale mixers was performed in 5-kg batches using an additional laboratory scale mixer in which 4.5 kg of PEDV-negative feed was added to the mixer and 500 mL of 10 5 TCID 50 /mL–diluted viral inoculum was added to create 5 kg of 10 4 TCID 50 /g–inoculated feed.…”
Section: Methodsmentioning
confidence: 99%
“…Bioassay procedures used were the same as those described previously ( Schumacher et al, 2016b ; Cochrane et al, 2017 ). Bioassay samples were selected after qRT-PCR analysis included a composite positive and negative control from laboratory and production-scale mixers, rice hull flush samples from the untreated, formaldehyde, and 2% MCFA flushes of the laboratory-scale mixers, as well as subsequent feed for all 4 laboratory-scale treatments ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…У рідких фекаліях на сонці вірус втрачає інфекційність протягом 6 год, в тіні -за 3 доби. Високі температури і прямі сонячні промені діють згубно (Jung and Chae, 2004;Thomas et al, 2014;Cochrane et al, 2017). В Україні зареєстровані і застосовуються різноманітні офіційні дезінфікуючі препарати проти інфекційних агентів різної природи.…”
Section: вступunclassified
“…Results from other studies suggest that specific thermal processing treatments, such as spray drying (a process using dry hot air to reduce the moisture of a particle) can reduce the survival of PEDV in porcine and bovine plasma by 5 log [ 6 , 7 ]. Other research has shown that conditioning and pelleting with temperatures above 54.4 °C could be effective in reducing infectivity of PEDV in swine feed [ 8 ]. However, the sole impact of thermal processing on the inactivation kinetics of PEDV in feed is still unknown.…”
Section: Introductionmentioning
confidence: 99%